Ombudsmandens personlige prægning af ombudsmandskontrollen - Gøtze, Michael (Politik, 2012)
The term ombudsman is a double reference and the ombudsman is thus a person as well as an institution. is applies for the Danish Parliamentary Ombudsman. In most legal theory on the ombudsman the institutional perspective is prevalent and the ombudsman is to a wide extent perceived through the same legal lenses as e.g. the courts as protectors of citizens’ rights. is approach is challenged in this article that focuses on the ombudsman as a person and as a personi ed control body. e following analysis comprises discussions of the personal element of the ombudsman vis-à-vis the selection of suitable cases and vis-à-vis the general interpretative strategies towards signi cant parts of the ombudsman review activities. Moreover, the article sheds light on the recent revision of the Danish ombudsman act limiting the employment period of a given ombudsman to ten years. e ombudsman is still appointed by the Parliament, however, and the ombudsman will continuously operate in a complex political-legal landscape.